KAJIAN PERSFEKTIF GENDER PEREMPUAN TANI DARI SUDUT EKONOMI PADA USAHATANI RUMPUT LAUT DI KABUPATEN BULUKUMBA - Asriyanti Syarif; Khaeriyah Darwis (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2018)
This research is to know the gender perspective of women farmers economically in the development of seaweed farming, analyze family income that involves women farmers in seaweed farming and the contribution of women farmers as wage labor (making stretches) on seaweed farming to increase family income, knowing welfare family and welfare of farmer women as wage laborers from seaweed farming, as well as knowing the influence / relationship between family income and women farmers to welfare.This research was done in Jalanjang Sub-district, Gantaang Kindang Subdistrict, and Bintarore Village, Ujung Bulu District, Bulukumba Regency, by taking a sample of 30 women farmers who doing seaweed farming with details of 15 people in Jalanjang Village and 15 people in Bintarore Village, Bulukumba Regency. This research done by calculating family income involving women farmers in seaweed farming, calculating women's income as a workforce making a stretch, the contribution of women farmers in increasing family income, calculating the welfare of families and women farmers, analyzing the welfare of families and women farmers to welfare. The results of this research are: (1) The role of peasant women experiences a shift and is expanding economically. In addition to being a family workforce, it also becomes wage labor (making a stretch) on other parties' farms. In terms of gender perspective on seaweed farming, it is seen that pre-farming, post-harvest and marketing activities have gender equality between husband and wife while in farming activities and harvest dominant husband's role. (2) Family income from seaweed farming is Rp. 1,583,566.67 / month while the income of women farmers as wage labor Rp.225,486.11 / month and contributed to the family income of Rp. 6.67%. (3) Family income is more feasible and belongs to the welfare category because income is greater than the poverty line issued by the BPS of the Bulukumba Regency of Rp. 2274,328 / month, while the income of farmer women is Rp.225,486.11 / month below the poverty line and is classified as non-prosperous, (4) family income correlates with welfare, while the income of women farmers do not correlate with welfare.